(untitled) (DARYAFT, 2025)
This article explores the challenges faced by Pakistani teachers of the Chinese language using the HSK Standard Course, focusing on the role of Urdu in teaching. With Chinese language education growing rapidly in Pakistan, especially under the Belt and Road Initiative, teachers encounter difficulties due to limited resources, curriculum gaps, and differences between Chinese and Urdu. Based on document analysis and teacher interviews, the study examines challenges related to the classroom environment, teaching materials, teacher preparedness, and student learning. The findings show that Urdu plays a key role in helping students understand and engage with Chinese. The article offers practical recommendations, including adapting the curriculum, improving teacher training, and using Urdu strategically to support learning. It concludes that policy support and pedagogical innovation are essential to enhance Chinese language education in Pakistan and strengthen Pakistan–China cooperation. Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified. Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies. Participant Consent: The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.